Inheritance Pattern of Infestation of Borer, Bruchus bilineatopygus Pic. (Coleoptera : Bruchidae), in Seeds of Albizia procera (Roxb.) Benth. - Roychoudhury, N.; Chawhaan, Pravin H.; Joshi, K. C.; Mandal, A. K. (Indian Forester, 2006)
The inheritance pattern of infestation and loss in seed yield due to a potential seed borer, Bruchus bilineatopygus Pic. (Coleoptera : Bruchidae), was quantified among open pollinated seeds of ten phenotypically superior trees (plus trees) of Albizia procera (Roxb.) Benth., collected from Bilaspur District of Chhattisgarh, India. Among the seeds of superior trees, entomological screening based on the level of borer infestation and loss in seed biomass revealed seeds of 2 trees namely PT-5 and PT-7 as highly resistant (< 5%), 4 trees namely PT-1, PT-2, PT-4 and Pt-6 as resistant (> 5 - < 10%), 3 trees namely PT-3, PT-8 and PT-10 as susceptible (> 10 - <20%) and only one tree namely PT-9 as highly susceptible (> 20%). Significant variations were noticed for the parameters included in the study. Small difference between phenotypic and genotypic coefficients of variation was observed for per cent infestation and loss in seed biomass. Heritability (broad sense) and genetic gain estimates were also high for these parameters suggesting that additive gene action is more important for these traits.